The Role of Anionic Polysaccharides in the Preparation of Nanomedicines with Anticancer Applications - M. Martínez, Ana; Benito, Marta; Pérez, Elena; María Teijón, José; Dolores Blanco, María (Current Pharmaceutical Design, 2016)
Cancer has become one of the main causes of death in developed countries, and it is expected to be declared as the disease with the highest worldwide morbidity and mortality indexes in the coming decades. Nanomedicine aims to overcome some problems related to this prevalent disease, particularly the lack of efficient diagnostic and therapeutic tools. The most recent scientific advances, which have conducted to a more personalized medicine, were focused on the production of nanocarriers involved into the transport and the delivery of drugs to targeted cells. A wide variety of nanocarriers composed by different materials have been designed for their use as drug delivery systems. Polysaccharides have emerged as very useful biopolymers among all raw materials used in the preparation of these nanoplatforms. They are highly stable, non-toxic and biodegradable molecules, and also present some chemical properties which are very difficult to reproduce using artificial polymers. Anionic polymers, such as hyaluronic acid, heparin or alginate, present some structural and chemical characteristics which make them ideal polymers to prepare nanosystems with anticancer applications. This review will focus on the description of some anionic polysaccharides and the possibilities they offer towards the preparation of nanosystems with applications in cancer treatment and diagnostics.
Keywords: drug delivery